Ferric citrate spans mineral metabolism and anemia domains in ESRD: a review of efficacy and safety data. Issue 6 (November 2014) - Sinsakul, Marvin; Rodby, Roger; Umanath, Kausik; Niecestro, Robert; Dwyer, Jamie P
<x xml:space="preserve">Abstract</x> Ferric citrate (Zerenex™, Keryx Biopharmaceuticals, Inc.), a phosphate binder drug candidate, recently completed a Phase III program confirming efficacy and demonstrating safety when used to treat hyperphosphatemia in patients with end-stage renal disease. Results of these trials demonstrate that ferric citrate effectively controls serum phosphorus and is well tolerated. Additionally, these studies demonstrate that ferric citrate improves iron parameters and reduces IV iron and erythropoietin stimulating agent utilization while maintaining hemoglobin levels. These unique features may further benefit the management of end-stage renal disease-related anemia.